1986
DOI: 10.1007/bf00614312
|View full text |Cite
|
Sign up to set email alerts
|

Curve-fitting in pharmacokinetics ? A comparison between gamma-and biexponential fits

Abstract: Seven sets of plasma concentration-time data were fitted to both a conventional biexponential equation and a gamma equation. The values of clearance (CL) and mean residence time (MRT) were calculated from the fitted parameters and compared with the values calculated by the trapezoid rule. Both the biexponential and gamma equations provided adequate fits to the data. The values of CL and MRT calculated from the biexponential fits correlated very closely with the values calculated by the trapezoid rule, but ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The present data show no significant effect of the method of modelling on mean derived parameters. This is in agreement with other data [32,33]. However, the wide 95% confidence intervals of the means show the variation which may be introduced when comparing different methods.…”
Section: Discussionsupporting
confidence: 92%
“…The present data show no significant effect of the method of modelling on mean derived parameters. This is in agreement with other data [32,33]. However, the wide 95% confidence intervals of the means show the variation which may be introduced when comparing different methods.…”
Section: Discussionsupporting
confidence: 92%
“…Plasma radioactive activities were then plotted as a function of time to create a time-activity curve to calculate for GFR. The GFR equation was determined by using bi-exponential fitting method [10]: GFR=Darea under time - activity curve=D0normalcfalse(normaltfalse)normaldnormalt, D is the dosage of injected 99m Tc-DTPA. The result was normalized by the body surface area which was calculated according to Dubois and Dubois [11].…”
Section: Methodsmentioning
confidence: 99%
“…The polyexponential function is : n C-I: (Xiexp(~it),~l<~, ,~ [4] i-I where n is the number of exponential terms, For ev data, to may be determined, after fitting, as a root of the equation in the range~. Functions were fitted using Hartley's modification of the Gauss-Newton algorithm (6).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Weiss (3) suggested the application of the gamma variate to fitting pharmacokinetic data obtained on both intravascular (iv) and extravascular (ev) dosing. Sainsbury and Ashley (4) compared the results of gamma variate and biexponential fitting and concluded that the gamma variate fitted their concentration-time data adequately but that exponential fitting was less susceptible to scatter in the data. However, this comparison was limited to iv dosing data for prenalterol.…”
Section: Introductionmentioning
confidence: 99%